Econometric Analysis of the Effects of Dividend Policy Changes on the Implied Cost of Equity Capital under Different Levels of Return on Assets - Aqaei, Sepideh; Arabzadeh, Meysam; Rezaei Pitenoei, Yasser; Ghodrati, Hassan; Kabiri , Mohammadtaghi (Business, Marketing, and Finance Open, 2026)
This study conducts an econometric analysis of the effects of changes in dividend policy on the implied cost of equity capital, considering the moderating role of return on assets (ROA). The main research question is whether the relationship between changes in dividend payouts and the cost of capital is influenced by the level of firm profitability. The primary objective is to test the hypothesis that the negative relationship between dividend increases and the cost of capital is stronger for firms with higher ROA. Methodologically, this is an applied research employing panel data from 120 companies listed on the Tehran Stock Exchange over an eight-year period (2016–2023). The implied cost of equity capital was calculated using the Gebhardt et al. model, and the relationships among the variables were examined using fixed-effects regression and interaction modeling. The findings revealed that, in the baseline model, an increase in dividend payouts leads to a decrease in the cost of capital. However, the key finding of the study indicated that this relationship alone is not statistically significant and is entirely moderated by firm profitability. The negative and significant coefficient of the interaction term between dividend changes and ROA confirmed that the mitigating effect of dividend increases on the cost of capital is considerably stronger and more reliable in firms with higher asset returns. This result suggests that firm profitability acts as a boundary condition determining how the market interprets dividend signals and, consequently, how the cost of capital responds.